Amplicon and Metagenomic Analysis of Middle East Respiratory Syndrome (MERS) Coronavirus and the Microbiome in Patients with Severe MERS - Waleed Aljabr; Muhannad Alruwaili; Rebekah Penrice-Randal; Abdulrahman Alrezaihi; Abbie Jasmine Harrison; Yan Ryan; Eleanor Bentley; Benjamin Jones; Bader Y. Alhatlani; Dayel AlShahrani; Zana Mahmood; Natasha Y. Rickett; et al. (mSphere, 2021)
Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in late 2012 in Saudi Arabia. The virus is a serious threat to people not only in the Middle East but also in the world and has been detected in over 27 countries.